2021
DOI: 10.1364/oe.415847
|View full text |Cite
|
Sign up to set email alerts
|

Rectangular multilayer dielectric gratings with broadband high diffraction efficiency and enhanced laser damage resistance

Abstract: Broadband multilayer dielectric gratings (MDGs) with rectangular HfO2 grating profile were realized for the first time using a novel fabrication process that combines laser interference lithography, nanoimprint, atomic layer deposition and reactive ion-beam etching. The laser-induced damage initiating at the grating ridge was mitigated for two reasons. First, the rectangular grating profile exhibits the minimum electric-field intensity (EFI) enhancement inside the grating pillar compared to other trapezoidal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…The PDMS mold was imprinted onto the resist (PMMA), spin-coated on the multilayer dielectric film mirror by UV nanoimprint lithography, and the resist grating structure opposite to the target HfO 2 grating structure was obtained. A rectangular diffraction grating with a diffraction efficiency of 95% (from 714 to 865 nm) and a damage resistance threshold of 0.59 J/cm 2 (40 fs) was fabricated [80].…”
Section: Nanoimprintingmentioning
confidence: 99%
“…The PDMS mold was imprinted onto the resist (PMMA), spin-coated on the multilayer dielectric film mirror by UV nanoimprint lithography, and the resist grating structure opposite to the target HfO 2 grating structure was obtained. A rectangular diffraction grating with a diffraction efficiency of 95% (from 714 to 865 nm) and a damage resistance threshold of 0.59 J/cm 2 (40 fs) was fabricated [80].…”
Section: Nanoimprintingmentioning
confidence: 99%
“…GWS are known to be a powerful solution to control key properties of light and in particular for tailoring the polarization and for realizing spectral and spatial beam shaping in high power laser systems. [14,15] The uniformity of the two key properties of GWS, period and linewidth (LW), is essential to achieve high optical efficiency. [16] Here, we come back to LIL because it is well suited for GWS fabrication due to its high period precision, if the dimensional variations caused by the Gaussian beam profile can be countered, especially for large-area GWSs.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of studies have been carried out to improve the LIDT of MLD gratings by optimizing the design, manufacturing, and cleaning processes. [4][5][6][7] The efforts were mainly devoted to the etching profile. Néauport et al demonstrated the significant impact of the etching profile on the electric field intensity (EFI) and the laser resistance.…”
Section: Introductionmentioning
confidence: 99%